The Analysis of Implementation of Information Technology in Knowledge Management Framework - JAIN, VIPIN; VERMA, RAJIV; SETHI, PUNEET (The journal of contemporary issues in business and government, 2021)
The global market condition and strategies of the organizations have been changing rapidly to coup the fluctuating circumstances of the business world. These change are being taken place due to the satirical movement or the rapid innovation in almost every sector of the businesses regardless of the size and market capitalization of the businesses. Therefore, it is very necessary for the corporate houses to amalgamate the such technological advancement that have capabilities to meet the current demand of organization to improve the working conditions. The solution of this has stopped at the implementation of the IT based technology or the upgrade the existing technologies with the help of the IT. Thus, outcome of this has emerged as the integration of the knowledge management with the IT and this will assist the managers to reduces the production input, and at the same time increase the productivity and net profit to the organization and even, make the business management easy than ever. This new implementation has been studies in this paper with the implementation of the Knowledge Management System (KMS).